Highly Innovative Drug Program in the Czech Republic: Description and Pharmacoeconomic Results-Cost-Effectiveness and Budget Impact Analyses - Ornstova, Eva; Sebestianova, Monika; Mlcoch, Tomas; Lamblova, Klara; Dolezal, Tomas (Value in health regional issues, 2018)
BACKGROUND: Highly innovative drugs (HIDs) can be granted 2 to 3 years of temporary reimbursement (TR) to provide timely patient access and to collect real-world evidence through registries in the Czech Republic. A TR applicant does not need to comply with cost-effectiveness (CE) requirements and the willingness-to-pay threshold. It is only when mandatory transition to permanent reimbursement (PR) status occurs does the drug need to comply with CE and willingness-to-pay requirements. OBJECTIVES: To describe and evaluate the HID program in the Czech Republic by analyzing the pharmacoeconomic results when a drug starts with TR status and transitions to PR status. METHODS: The study was a retrospective analysis of reimbursement decisions of HIDs. All drugs approved for TR (valid from January 2008 to January 2018) were identified. A description of the HIDs and their pharmacoeconomic results were analyzed. RESULTS: Fifty TR drugs were identified. Most (68%) were oncology drugs and 44% were orphan drugs. After the expiration of their TR status, 83% were successfully transitioned to PR status. Cost-utility analysis was used to support CE results in 42% of the TR drugs. The mean incremental cost-effectiveness ratio (cost/quality-adjusted life-year) of drugs that entered TR status was €97,868. When the time came for transition to PR status, the mean incremental cost-effectiveness ratio was €34,086 (lower by 65%). Net budget impact increased by 3% and decreased by 25% in the first and fifth years, respectively, after applying for PR. CONCLUSIONS: This analysis provides better insight into the HID program for costly innovative drugs over a 10-year follow-up. A successful transition to PR status was observed for most of the HIDs (83%).
Keywords: Orphan Drug Production; Quality-Adjusted Life Years; Česká republika; náklady na léky; Cost-Benefit Analysis; vládní regulace; Retrospective Studies; Government Regulation; lidé; léčivé přípravky; dávkové mechanismy; Pharmaceutical Preparations; Czech Republic; ekonomika farmaceutická; výroba orphan drugs; analýza nákladů a výnosů; Drug Costs; Humans; kvalitativně upravené roky života; Economics, Pharmaceutical; Reimbursement Mechanisms; retrospektivní studie